Caries experience in young children with congenital heart disease in a developing country - Pimentel,Elizangela Lins Cavalcanti (2013)
Oral care is frequently suboptimal in children from developing countries, especially those suffering from severe systemic diseases. The aim of the present study was to analyze the oral epidemiological profile of 3-to-5-year-old children with congenital heart disease. Dental and medical records of children evaluated at the Dental Service of the National Institute of Cardiology, Rio de Janeiro, Brazil, were reviewed. Caries experience was reported using the dmft index. Negative behavior towards dental management was recorded. The sample consisted of 144 children aged 4.41 ± 0.95 years. The mean dmft value was 5.4 ± 4.9, and 80.5% had at least one caries lesion. Dmft index was greater in the presence of cyanotic cardiac disease and in children with negative behavior. An increase in the “missing” component of the dmft index was also found in children using medicine on a daily basis. A higher caries experience was associated with children whose fathers had only an elementary education. In conclusion, children with congenital heart disease had high levels of caries experience at a young age. Cyanosis, negative behavior, daily use of medicine, one-parent family and the educational level of fathers seem to influence caries experience in children with congenital cardiac disease.